Mesoscale Eddies Observed at the Denmark Strait Sill. Issue 11 (19th November 2019) - Moritz, Martin; Jochumsen, Kerstin; North, Ryan P.; Quadfasel, Detlef; Valdimarsson, Héðinn
Abstract: The Denmark Strait overflow is the major export route of dense water from the Arctic Mediterranean into the North Atlantic. At the Strait's shallow sill, the overflow is a bottom‐intensified cold and dense plume, bound to the east by a thermal front formed with the warmer, northward flowing North Icelandic Irminger Current. More than two decades of observations at the sill show strong fluctuations of volume flux on daily time scales. To better understand the source of this variability, a five‐mooring array was installed at the sill, capturing nearly 1 year of velocity and bottom temperature measurements at a high temporal and spatial resolution. Bottom temperature fluctuations that exceed 4 °C indicate a meandering of the front between the plume and the North Icelandic Irminger Current. Current vector rotation shows trains of alternating cyclones and anticyclones at the sill. An eddy crosses the sill every 3 to 6 days with a mean velocity of 0.4 m/s and a typical diameter of 30 to 40 km. The results suggest that anticyclones, with centers passing through the deepest part of the sill, may be responsible for periods of increased volume flux—also referred to as boluses and pulses in previous studies. Although the relationship between eddies, pulses, and boluses is still unclear, the results show that eddies are directly linked to fluctuations in the strength, thickness, and position of the overflow plume. Plain Language Summary: The southward flow of dense water from the Arctic ocean plays a crucial role in global ocean circulation but is almost immediately constrained on its way south by a submarine ridge that connects Greenland, Iceland, the Faroe Islands, and Scotland. The southward flow is therefore forced to pass through several straits and up and over relatively shallow sills. Most of the flow passes over a sill in the Denmark Strait, located between Greenland and Iceland. In this study, we present observations from an array of instruments, which measure the southward flow as it passes over the Denmark Strait sill. The flow is characterised by trains of eddies (vortices), with an alternating sense of rotation; meaning a counterclockwise eddy is usually followed by a clockwise eddy. The eddies are 30 to 40 km wide and need about 1 day to pass over the sill. These eddies help to explain pronounced changes in the flow across the sill, as they can help either to speed up the flow or slow it down. The results of this study contribute to understanding mesoscale fluctuations, which influence local mixing processes and water mass transports. Key Points: Mesoscale flow variability is observed at the Denmark Strait Sill with a five‐mooring array Trains of alternating eddies are passing the sill Anticyclones are found to be related to the occurence of boluses and pulses